A Review of the Potential of Poly-(lactide-co-glycolide) Nanoparticles as a Delivery System for an Active Antimycobacterial Compound, 7-Methyljuglone - Bianca Diedericks; Anna-Mari Kok; Vusani Mandiwana; Namrita Lall (MDPI AG, 2024)
7-Methyljuglone (7-MJ) is a pure compound isolated from the roots of Euclea natalensis A. DC., a shrub indigenous to South Africa. It exhibits significant promise as a potential treatment for the highly communicable disease tuberculosis (TB), owing to its effective antimycobacterial activity against Mycobacterium tuberculosis. Despite its potential therapeutic benefits, 7-MJ has demonstrated in vitro cytotoxicity against various cancerous and non-cancerous cell lines, raising concerns about its safety for consumption by TB patients. Therefore, this review focuses on exploring the potential of poly-(lactide-co-glycolic) acid (PLGA) nanoparticles as a delivery system, which has been shown to decrease in vitro cytotoxicity, and 7-MJ as an effective antimycobacterial compound.